The life impossible : a novel [compact disc, unabridged] - Haig, Matt, 1975- (Penguin Audio, 2024)
Grace Winters is a widow and retired math teacher whose life seems to be getting smaller and smaller. She keeps out of the way of people and passes time watching the birds in her garden and doing crossword puzzles. But when a long-lost friend dies in strange circumstances and leaves her a house on the Spanish island of Ibiza, Grace's solitary existence drastically changes.